Arcabouço de compilação para linguagens de especificação ASM - Mario Celso Candian Lobato (2006)
The ACOA framework is a framework for implementing compilers. The ACOA automatically builds lexer, parser and classes of abstract syntax tree nodes (AST) and uses Aspect-Oriented Programming to implement semantics analysis and code generation. The objective of the ACOA is to be of easy use for implementing compilers and to allow easy alterations in the compilers implemented by means of the framework.